ChatGPT: Where Is a Silver Lining? Exploring the realm of GPT and large language models - Elena Tikhonova; Lilia Raitskaya (National Research University Higher School of Economics, 2023)
Introduction: the JLE editors analyse the scope and depth of the subject area of ChatGPT and related topics based on the Scopus database. The Scopus statistics prove a skyrocketing rise in the number of publications in the field in question during 2023. The major alarming themes cover authorship and integrity related to AI-assisted writing, threats to educational practices, medicine, and malevolent uses of ChatGPT. Keywords Explained: the key terminology is defined, including generative pre-trained transformers (GPT); ChatGPT; artificial intelligence (AI); AI chatbots; natural language processing (NLP); large language models; Open AI; large language model (LLM). International Research on ChatGPT: as of September 24 2023, the Scopus database has indexed 1,935 publications, with "ChatGPT" in the title, abstract, or keywords. A skyrocketing rise in the number of research has been reported since the early days of 2023. 1,925 indexed publications out of 1,935 were published in 2023. Most of them came from the USA, India, the UK, and China. The number of documents indexed in the Scopus database as well as PubMed,  arXiv and others are exponentially rising. ChatGPT in Education: the academic community has been actively discussing the challenges education will face in the era of ChatGPT in the context of the fundamental threats posed to the educational system. The latter include assessment procedures, information accuracy, and skill devaluation. As many complex technologies, generative pre-trained transformers are ambivalent in nature, providing a great potential for learning and education at large, including new approaches based on critical thinking and awareness of the pros and cons of AI. ChatGPT in Science: great prospects for text generation and improvements in language quality adjoin to dubious authorship and potentially inconsistent and erroneous parts in the AI-produced texts. Publishers and journals are working out new publishing policies, including publishing ethics towards AI-assisted or AI-improved submissions. Conclusion: JLE is planning to revise its editorial policy to address the new challenges from AI technologies. JLE editors welcome new submissions of research articles and reviews as well as special issues on ChatGPT and related themes, with potential applications of chatbots in education, innovative approaches to writing assignments, facilitating personalized learning, academic integrity issues related to AI-supported writing, etc. in focus.